1990
DOI: 10.1099/00207713-40-4-452
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Description of Pseudomonas cocovenenans (van Damme, Johannes, Cox, and Berends 1960) NCIB 9450T and Strains Isolated from Cases of Food Poisoning Caused by Consumption of Fermented Corn Flour in China

Abstract: Phenotypic and genetic characteristics of Pseudomonas cocovenenans NCIB 9450T (T = type strain) and strains isolated from cases of food poisoning caused by consumption of fermented corn flour are compared. Our results show that these strains are members of the same species and conform to the description of Section I1 of the genus Pseudomonas. Because of small differences in substrate utilization patterns, the strains isolated in the People's Republic of China are thought to be biovars of P . cocovenenans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…In 1988 Gwynn et al (3) also identified and described P. cocovenenans, as a producer of a new member of the monobactam family of antibiotics, and their experimental results were very similar to ours (16,17).…”
supporting
confidence: 75%
See 3 more Smart Citations
“…In 1988 Gwynn et al (3) also identified and described P. cocovenenans, as a producer of a new member of the monobactam family of antibiotics, and their experimental results were very similar to ours (16,17).…”
supporting
confidence: 75%
“…The phenotypic characteristics were determined by methods described in the Manual of Methods for General Bacteriology (2) and the methods of Stanier et al (9). The phenotypic characteristics were the same as those described previously by us (16) and others (3) except for some additional ones and revised ones as follows. Oxidase reaction was weakly positive as described in our previous article, but it was scored as negative, although it was different from the true negative reaction as in Enterobacfer spp.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…[Pseudomonas] rRNA group I1 (43) is also part of rRNA superfamily 111, where it constitutes a separate cluster that is only remotely related to the Comamonadaceae (18) [8], [Pseudomonas] syzygii [50], and [Pseudomonas] cocovenenans [74]) have also been described as members of the so-called solanacearum rRNA group (68 …”
mentioning
confidence: 99%